2001
DOI: 10.1128/iai.69.7.4667-4672.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Encoding Th1 Cell-Activating Cytokines and Lymphoid Homing Chemokines by Chlamydia-Pulsed Dendritic Cells Correlates with Protective Immunizing Efficacy

Abstract: We studied the expression of cytokines, chemokines, and chemokine receptors by the RNase protection assay in chlamydia-pulsed dendritic cells to better understand their potent anti-chlamydial immunizing properties. We found that chlamydia-pulsed dendritic cells express a complex profile of inflammatory and immunomodulatory molecules. These include CCR-7, interleukin-12, and interferon-induced protein 10, molecules that might influence the homing of pulsed dendritic cells to the site of chlamydial infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Su et al (54) demonstrated that the adoptive transfer of bone marrow-derived DCs pulsed ex vivo with nonviable C. trachomatis induced protective immunity comparable to that induced by live C. trachomatis infection. The use of nonviable C. trachomatis naturally focused this and later studies on the CD4 ϩ T cell response to C. trachomatis (55). The CD8 ϩ T cell response remained unobserved in these studies because cytosolic localization of protein Ags was thought to be required for stimulating CD8…”
Section: Discussionmentioning
confidence: 99%
“…Su et al (54) demonstrated that the adoptive transfer of bone marrow-derived DCs pulsed ex vivo with nonviable C. trachomatis induced protective immunity comparable to that induced by live C. trachomatis infection. The use of nonviable C. trachomatis naturally focused this and later studies on the CD4 ϩ T cell response to C. trachomatis (55). The CD8 ϩ T cell response remained unobserved in these studies because cytosolic localization of protein Ags was thought to be required for stimulating CD8…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Antigen-pulsed mature DCs express genes that induce DCs migration, activation and recruitment of T cells, 37 and different antigens phagocytosed by DCs induce different patterns of cytokine production by CD4 þ T cells, depending on the cytokines produced by the DCs. 34 The availability of DC-derived IL-12 is a requirement for the development of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21). The important role of DC in initiation and maintenance of T cell responses to chlamydial infection has been demonstrated by several previous studies using mouse models of C. trachomatis mouse pneumonitis strain, more recently called Chlamydia muridarum (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Su et al (22) reported that i.v.…”
mentioning
confidence: 99%